Penerapan Green Constitution di Indonesia dalam Upaya Menjaga Keberlangsungan Lingkungan Hidup yang Baik dan Sehat sebagai Tanggung Jawab Negara - Athar Tristan Andana Kanz; Githa Asmadeningrum Rosady; Savero Pramudika Arya Wibowo (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
An important element of life on earth is the environment, which consists of everything, conditions and influences that exist in the area where humans live and have an impact on life. Everything that forms life, namely objects, energy, the environment, living creatures, humans and their actions, and living space are included. These items are closely related to each other and interact with each other. This research is included in the library research category because the data is collected from written sources such as books, articles, magazines, newspapers, scientific journals and libraries. This approach allows researchers to obtain precise and relevant data by utilizing various library sources. Library research techniques are used to find legal sources that are trustworthy and relevant. The state is tasked with maintaining a clean and healthy environment, in accordance with Indonesia's current Green Constitution. Article 28H paragraph (1) emphasizes the right of every citizen to a good and healthy living environment in addition to the right to physical and spiritual well-being. This idea is represented in various articles of the 1945 Constitution. Strengthening the legal basis for environmental management and preservation, Law Number 32 of 2009 concerning Environmental Conservation and Management offers a more complete picture of the environment. The living environment as referred to in Article 1 point 1 is a spatial unity consisting of all physical and biological components that have an impact on nature and life, including humans and their behavior.